Experimental and numerical studies for applying hybrid solar chimney and photovoltaic system to the solar-assisted air cleaning system. (1st July 2020) - Huang, Ming-Hua; Chen, Lei; Lei, Le; He, Peng; Cao, Jun-Ji; He, Ya-Ling; Feng, Zhen-Ping; Tao, Wen-Quan
Highlights: Small test setups for both pure and hybrid solar chimney system are built. A numerical simulation method for the hybrid system is proposed and validated. Hybrid systems greatly increase the total power output. Hybrid systems can reduce land requirement of the solar-assisted air cleaning system. Abstract: Under the background of global energy shortage and environment deterioration, researchers of the world pay high attention to develop renewable energy. This paper proposes a hybrid solar chimney and photovoltaic system for the novel solar-assisted air cleaning system. Small-scale laboratory setups are designed and fabricated. Experimental results reveal that replacing 50.60% acrylic glass of the collector top with photovoltaic panels will reduce the thermal air flow rate only by 14%, but generate significant electric power output. A three-dimensional numerical simulation model is established and validated by experimental results (air flow rate, temperature distribution). The model includes solar ray tracing model, surface to surface radiation model, buoyancy-driven flow and heat transfer model and power generation model. Then, this model is used to predict a large-scale system based on the Manzanares pilot power plant in Spain. For the large-scale system, the electrical energy generated by the photovoltaic panels can be used to drive suction fans to increase air input. Covering the entire top surface of the collector by photovoltaic panels (113-meter-wide), the total air flow rate would increase to 2.21 times compared with the system without photovoltaic panels. And setting photovoltaic panels on the collector bottom with 113-meter-wide, the total air flow rate would increase to 2.42 times. Thus, adding photovoltaic panels for the collector can greatly improve the utilization of solar energy. It can increase the amount of air purification, or reduce land requirement for the same flow rate.